Development of an evaluative framework promoting a paradigm shift towards resource recovery in wastewater treatment - Coothen, Yuva (Department of Civil Engineering, 2023)
Resource recovery from wastewater is a rapidly emerging research area promoting the development of several technologies that have the potential to increase the sustainability of process operations in wastewater treatment. With the implementation of appropriate treatment technologies, nutrients such as phosphorus and nitrogen can be recovered from nutrient rich sludge dewatering liquor in various forms to be used as agricultural fertilisers; portion of power demands at WWTPs can be offset by extracting energy from wastewater; the undesirable impact of wastewater treatment processes on air quality from emission of greenhouse gases, on land from sludge disposal and on downstream water bodies via effluent discharge can be mitigated. The performance of WWTP design and control strategies can be evaluated, based on their impact on downstream water bodies and the associated net operational costs of each unit operation, by using the performance indices developed by the IWA BSM task group. With the impact of products generated from WRRFs on air quality and land, the value of resources recovered, and other operational costs being overlooked in the current evaluation system, it is unclear whether the fate of products generated from WRRFs would influence the design and operation of WWTPs. This dissertation addresses the hypothesis that a WWTP model evaluative framework that considers the fate of WWTP products and value of resources that can potentially be recovered from WRRFs will generate a useful tool for design and operation of WWTPs in South Africa and aid in their transition to future WRRFs. To fill the gaps in the current evaluation system, it was important to extend the term “effluent” to be now inclusive of greenhouse gases that evolve from WWTPs and sludge disposed. As such, two new evaluative equations were formulated accordingly (EQIgas and EQIsludge) in addition to the existing effluent quality index now known as EQIwater. The latter has been modified such that the weighting assigned to each pollutant is a function of the regionspecific or WWTP-specific pollutant concentration limits. This flexibility allows the EQIwater evaluation to be tailored towards the effluent quality goals specific to each plant or region. The EQIgas is function of the greenhouse gasses that evolve from WWTPs with weighting factors set equal to their respective global warming potentials. The EQIsludge was formulated based on the South African sludge disposal guidelines taking into consideration the stability, pollutant and microbiological classes. Additionally, the existing operational cost index was modified to include fines for violation of pollutant limits in the effluent, the monetary benefits of nutrient recovery and dosing of additives such as lime or magnesium. The PWM_SA by Ikumi et al. (2015a) was used to replicate Module 4 of Waterval WCW for the simulation of two scenarios: (1) without side-stream treatment and (2) with side-stream treatment including recycle of side-stream effluent to head of works. Due to model limitations, the effluent quality evaluation was limited to the EQIwater. On the other hand, fines for noncompliance to effluent regulations and cost recovered from the sale of struvite were not considered in the OCI evaluation since the determination of an appropriate future unit cost for each component in a South African context was outside of the scope of this project. From the simulated results, it was noted that Module 4 of Waterval WCW has sufficient capacity to treat the influent wastewater as well as the recycled sludge dewatering liquors generated from that module to acceptable quality with respect to the standards of the Waterval Water Use License (08/C22C/fg/646). Thus, the implementation of side-stream struvite precipitation in this case significantly increases the net operational costs for marginal benefits in terms of effluent quality. The extended performance indices framework is currently being implemented, as an evaluative protocol, in the simulation of all considered strategic scenarios in order to determine the most impactful in future decision making for the given WRRF systems. However, in order for this evaluative framework to be more effective, the models will require modifications, such that the predictions made regarding system performance include the variables of significance, related to prioritised criteria for the products generated by the system.